2019
DOI: 10.1016/j.sjbs.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Natural products of Alternaria sp., an endophytic fungus isolated from Salvadora persica from Saudi Arabia

Abstract: This study is to evaluate the potential of endophytic fungi of Salvadora persica for the production of bioactive compounds against pathogenic bacteria and fungi. Forty-two fungal isolates were obtained from 135 young and old stem and 125 root segments. Those 42 isolates representing ten fungi include: Trichoderma sp. (the most common), two species of Alternaria , Rhizopus arrhizus and 6 sterile mycelia. The ten fungi we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The compounds found in Dendrobium, including dendrobine and related compounds, can boost human immunity besides preventing and improving metastatic cancer and have shown promising therapeutic effects on Alzheimer's disease (Nie et al, 2016). This medicinal plant has been used to prevent or treat illnesses owing to the presence of bioactive compounds in their cells and have been added to drugs since ancient times (Elgorban et al, 2019). However, dendrobine is not produced in large quantities by the D. nobile plant species because of its slow growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds found in Dendrobium, including dendrobine and related compounds, can boost human immunity besides preventing and improving metastatic cancer and have shown promising therapeutic effects on Alzheimer's disease (Nie et al, 2016). This medicinal plant has been used to prevent or treat illnesses owing to the presence of bioactive compounds in their cells and have been added to drugs since ancient times (Elgorban et al, 2019). However, dendrobine is not produced in large quantities by the D. nobile plant species because of its slow growth.…”
Section: Introductionmentioning
confidence: 99%
“…reported the possible industrial production of paclitaxel (1124.34 µg/L) under optimized fermentation conditions. A gibberellin-producing Penicillium commune strain has been recovered from the Sesamum indicum plant (Elgorban et al, 2019). Many fungal endophytes have the potential to biosynthesize numerous bioactive natural compounds that may indirectly or directly be applied as therapeutic mediators in the treatment of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…were frequently isolated more than others endophytes. Elgorban et al (2019) also showed Alternaria sp. as the prospective endophytic fungi from Salvadora persica for the production of bioactive compounds against pathogenic bacteria and fungi.…”
Section: Discussionmentioning
confidence: 96%
“…were restricted to stem only whereas Aspergillus sp., C. herbarum to leaves only [ 118 ]. A total of 35 isolates of endophytic fluorescent Pseudomonas were identified from the leaves, shoot, and root samples of both S. persica and S. oleoides [ 119 ] Young and old stem and 125 root segments were processed for the isolation of endophytes and resulted in forty-two fungal isolates namely, Trichoderma sp., 2 species of Alternaria , Rhizopus arrhizus and 6 sterile mycelia [ 120 ].…”
Section: Endomicrobial Diversity Of Important Medicinal Plants/genusmentioning
confidence: 99%